ALGORITHM ANALYSIS TO DETERMINE THE ORDER OF GOODS AT THE COMPANY PT. SAGAMI INDONESIA MEDAN - Amran Sitohang; Olven Manahan (INFOKUM, 2021)
The amount of competition in the business world, especially in the electronics industry, requires developers to find a strategy that can increase product orders at electronic companies. With daily printing activities, the data will increase over time. The data not only serves as an archive for the company, the data can be utilized and processed into useful information for increasing product orders. The data not only serves as an archive for the company, the data can be utilized and processed into useful information for increasing product orders. Apriori algorithm is a market basket analysis algorithm that is used to generate association rules. Association rules can be used to find a relationship or cause and effect. Association rules can be generated with a priori algorithm. An a priori algorithm that aims to find frequent itemsets is run on a set of data. Market basket analysis is one of the techniques of data mining that studies consumer behavior in buying goods simultaneously at one time. The purpose of this research is to analyze product order data to form a pattern of itemsets combination using a priori algorithm, to form rules with association rules, to implement data mining by using Tanagra 1.4 tools. Stages of this research method have several stages including literature study, field research (field research), analysis, discussion of analysis based on the method used,